2018
DOI: 10.12973/iji.2018.1128a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Handep Cooperative Learning Based on Indigenous Knowledge on Mathematical Problem Solving Skill

Abstract: Indigenous people of Dayak tribe in Kalimantan, Indonesia have traditionally relied on a system of mutual cooperation called handep. The cultural context has an influence on students mathematics learning. The handep system might be suitable for modern learning situations to develop mathematical problem-solving skill. The objective of the study was to investigate the effect of handep cooperative learning model compared to problem-based learning model on mathematical problem-solving skill of rational exponent ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 17 publications
2
23
0
8
Order By: Relevance
“…Salah satu tolok ukur dari keunggulan tersebut adalah penguasaan atas keterampilan-keterampilan abad 21. Keterampilan tersebut meliputi critical thinking and problem solving; creativity and innovation; communication; dan collaboration atau yang sering dijargonkan dengan 4C (Demitra & Sarjoko, 2018). Pemecahan permasalah menjadi hal mendasar dasar yang harus ditumbuh kembangkan.…”
Section: Pendahuluanunclassified
“…Salah satu tolok ukur dari keunggulan tersebut adalah penguasaan atas keterampilan-keterampilan abad 21. Keterampilan tersebut meliputi critical thinking and problem solving; creativity and innovation; communication; dan collaboration atau yang sering dijargonkan dengan 4C (Demitra & Sarjoko, 2018). Pemecahan permasalah menjadi hal mendasar dasar yang harus ditumbuh kembangkan.…”
Section: Pendahuluanunclassified
“…A t-test was uased to ensure equality. Before applying the t-test, the normality test was analyzed using Kolmogorov-Smirnov technique and their homogeneity using Levene technique (Demitra & Sarjoko, 2018). Meanwhile, in the qualitative phase some students were intentionally chosen to participate in the study.…”
Section: Participantsmentioning
confidence: 99%
“…Before doing the Manova-test, the variables of the data was tested, the homogeny of variance/covariance matrices of dependent variables, and the correlation between the dependent variables were also examined (Akayuure et al, 2016;Candiasa, 2010). The bivariate normality test was analyzed using correlation using the mahalanobis distance technique (Burdenski Jr, 2000;Demitra & Sarjoko, 2018). Furthermore, the homogeneity test of variance-covariance matrix of dependent variables using Box'M test (Akayuure et al, 2016).…”
Section: Quantitative Data Analysismentioning
confidence: 99%
“…However, Lee et al (2014) found that many fourth-grade students had difficulty in solving mathematical problems. Supportively, in Indonesia, Demitra and Sarjoko (2018) and Parwati et al (2018) revealed that mathematical problem-solving skills of primary and secondary school students need to be improved. Students generally learn to solve structured problems related to the subject matter (Johnson et al, 2011;Yu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%